On the accuracy of the nearly PML for nonlinear FDTD domains - Ramadan, O (IEEE-Inst Electrical Electronics Engineers Inc, 2006)
In this letter, the first implementation of the nearly perfectly matched layer (NPML) for truncating nonlinear dispersive finite-difference time-domain (FDTD) grids is presented. In the proposed method, the Z-transform theory is employed in the FDTD implementations of the NPML formulations. e performance of the NPML was investigated through a numerical example carried out in two-dimensional Kerr-Raman nonlinear and Lorentz-dispersive domain, and it has been observed that the NPML is capable of absorbing nonlinear electromagnetic waves.
Keywords: dispersive; finite difference time domain (FDTD); nearly perfectly matched layer (NPML); nonlinear; Z-transform